Pengaruh Pemahaman Pendidikan Hukum terhadap Perilaku Bermedia Sosial Mahasiswa PPKN FKIP Universitas Lampung - Kayla Zahara Salsabila; Hermi Yanzi; Devi Sutrisno Putri; Berchah Pitoewas; Fitra Endi Fernanda (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of legal education understanding on the social media behavior of students of the Civic Education Study Program (PPKn), Faculty of Teacher Training and Education, University of Lampung. This research employs an ex post facto method with a quantitative descriptive correlational approach. The subjects of this study were students of the PPKn Study Program at the University of Lampung, cohort of 2022. The sample consisted of 52 students selected through purposive sampling technique. Data were collected using tests and questionnaires. The data analysis technique used in this study was simple linear regression analysis. The results of the study indicate that legal education understanding has an effect on students’ social media behavior. This is evidenced by the results of the simple linear regression test, which show that the F-value is 35.704 with a significance value of 0.000 (< 0.05) and a regression coefficient of 1.619. The coefficient of determination (R²) is 0.417, indicating that legal education understanding contributes 41.7% to students’ social media behavior. These findings demonstrate that legal education understanding has a positive and significant effect on students’ social media behavior.